Equity Valuation of Brunello Cucinelli S.p.A. - Pacitto, Jacopo (2023)
The goal of this thesis is to determine a fair price per share for Brunello Cucinelli, as well as provide a recommendation to buy, hold, or sell the stock based on the market price on May 25, 2023, which is €78,95. To achieve this, a thorough evaluation of the business was conducted, including an industry, macroeconomic and business analysis, followed by a financial analysis of past performance. The share price was determined using three different DCF models: Asset Side, Adjusted Present Value, and Equity Side. A sensitivity analysis was also conducted to account for assumptions uncertainty. Based on these factors, a sell recommendation was made with a result of €60 per share. This result was compared to Kepler Cheuvreux's result of €63 per share on January 10, 2023.